Family Education Training To Prevent Sexual Abuse Of Children In Kenagarian Pangkalan District Pangkalan Koto Baru Regency Limapuluhkota - Indah Sukmawati; Afdal Afdal; Miftahul Fikri; Gusni Dian Suri; Yessa Maulida (Universitas Negeri Padang, 2023)
Cases of sexual abuse against children experienced a significant upward trend, where from 11,952 cases in 2021 it increased by 34.62% to 16,114 cases in 2022. West Sumatra Province itself is in seventh place in the province with the most reported cases of sexual abuse against children, and the district Fifty cities, based on BPS data from West Sumatra Province, are in first place with the most reported cases of sexual harassment. The results of interviews with several parents in Pangkalan Limapuluh Kota Regency show that parents do not yet have the ability to provide education to prevent sexual abuse in children. This training is provided using lecture, discussion and direct practice methods regarding family education to prevent sexual abuse of children. In the initial evaluation, the results showed that almost all of the training participants stated that they had never provided sexual education to children at home. Then in the final evaluation the results were obtained that they gained knowledge and ways to provide sexual education to children to prevent sexual harassment. Training participants also know how important social support in the family is for children who are victims of sexual abuse.